Kontribusi Psychological Capital terhadap Stabilitas dan Efektivitas Organisasi Pasca Pandemi: Systematic Literature Review - Egalita Shaumi Mumtaz; Agnesia Daniela Lumunon (INDO PUBLISHING, 2026)
The COVID-19 pandemic created high uncertainty that threatened organizational stability, necessitating strategic psychological resources for recovery. This study examines the importance of Psychological Capital (PsyCap) in supporting organizational stability and effectiveness post-crisis. The research hypothesis states that PsyCap contributes positively to organizational resilience, employee performance, and adaptability. The method employed is a Systematic Literature Review of recent relevant scientific journals. The results indicate that PsyCap significantly enhances coping mechanisms, organizational agility, and change readiness, while reducing job insecurity. This influence is found to be stronger in the healthcare, tourism, and education sectors. In conclusion, PsyCap serves as a crucial strategic asset for organizational sustainability and effectiveness amidst post-crisis dynamics.